2022
DOI: 10.3390/nu14173571
|View full text |Cite
|
Sign up to set email alerts
|

Different Effects of Low Selenite and Selenium-Nanoparticle Supplementation on Adipose Tissue Function and Insulin Secretion in Adolescent Male Rats

Abstract: Adolescence is a period of intense growth and endocrine changes, and obesity and insulin-resistance processes during this period have lately been rising. Selenium (Se) homeostasis is related to lipid metabolism depending on the form and dose of Se. This study tests the actions of low-dose selenite and Se nanoparticles (SeNPs) on white (WAT) and brown adipose tissue (BAT) deposition, insulin secretion, and GPx1, IRS-1 and FOXO3a expression in the WAT of adolescent rats as regards oxidative stress, adipocyte len… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
22
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(30 citation statements)
references
References 95 publications
8
22
0
Order By: Relevance
“…In recent years, the ability of Se NPs for autophagy regulation has been proved to show strong potentials in some impotent diseases, including cancer, tuberculosis, rheumatoid arthritis, adolescent obesity or anorexia, skin diseases, diabetes and kidney injury. The attractive bioactivity of Se NPs for autophagy modulation not only suggests Se NPs for disease treatment alone ( 78 , 79 ), but also introduces the possibilities to combine Se NPs and current chemotherapeutics to achieve enhanced efficiency ( 70 , 71 ), which would be beneficial in facilitating the development of new therapies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In recent years, the ability of Se NPs for autophagy regulation has been proved to show strong potentials in some impotent diseases, including cancer, tuberculosis, rheumatoid arthritis, adolescent obesity or anorexia, skin diseases, diabetes and kidney injury. The attractive bioactivity of Se NPs for autophagy modulation not only suggests Se NPs for disease treatment alone ( 78 , 79 ), but also introduces the possibilities to combine Se NPs and current chemotherapeutics to achieve enhanced efficiency ( 70 , 71 ), which would be beneficial in facilitating the development of new therapies.…”
Section: Discussionmentioning
confidence: 99%
“…However, there are still lots of critical issues for the further clinical application of Se NPs by regulating autophagy. Firstly, although some works have indicated the potential mechanisms of Se NPs induced autophagy, most of these works just provided some phenotype results without depth investigations ( 68 , 75 , 78 ). To further confirm the detailed mechanisms of Se NPs induced autophagy, knockout/knockdown experiments in cell and mice models are needed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Correct oxidative balance is deeply related to the endocrine signaling process and cell proliferation and differentiation [4]. It has been recently found that Se is deeply related to white adipose tissue (WAT) metabolism during adolescence [5]. However, its effects clearly differ depending on the form of administration.…”
Section: Introductionmentioning
confidence: 99%
“…This treatment decreased insulin signaling and increased forkhead box O3a (FOXO3a), affecting autophagy and lowering inflammation. However, since both forms of Se administration increased the activity of the antioxidant enzyme GPx1 in the same way, it is inferred that their contrasting effects on WAT adipocytes are GPx1-independent [5]. Therefore, there must be additional factors that contribute to these deep changes in lipid homeostasis.…”
Section: Introductionmentioning
confidence: 99%